Elite level development rates and age-based performance patterns for the men's throwing events - Babitt, D.; Saatara, M. (New Studies in Athletics, 2014)
In addition to differences in rates of progression among individual athletes, it is known that each event has its own average development profile. The purpose of this study was to provide guidelines to athletes and coaches in each of the men's throwing events by examining the performances of the athletes who have dominated at recent Olympic Games and IAAF World Championships in Athletics. The authors, both experienced coaches, analysed the age and yearly best performances of sample groups of 23 or 24 performers active in each of the four events since 2005. They found, for example, that on average world-class men's javelin throwers maximise their performance at a younger age than athletes the other men's throwing events and that while elite men's discus and hammer throwers display slower development, they have smaller drop-offs in performance after their peaks are reached. The authors' data is presented in tables that provide benchmark percentages of eventual personal bests at each age in each of the four events for throwers aspiring to world-class.